HARMONY OF ARTISTIC AND TECHNICAL FACTORS IN THE PROCESS OF PERFORMING MUSIC (Multidisciplinary Journal of Science and Technology, 2026)
This article extensively discusses the issue of the harmony of artistic expression and technical skill in the process of musical performance. The issues of the performer's artistic thinking, technical preparation, psychophysiological state, and interpretation on stage are analyzed scientifically and theoretically. Also, based on pedagogical experience, ways of forming artistic and technical factors as a whole are revealed.